2015
DOI: 10.1016/j.techsoc.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterising product-service systems in the healthcare industry

Abstract: Since the 1970s, marketing and innovation management communities have been investigating how to incorporate customer-desired functions into new product and service designs. These wide-ranging enquiries have shed light on the impact of lead-user engagement in new product development, demonstrated ways to examine service production and delivery, such as the use of 'line of visibility' in service blueprints and the modelling of 'service encounters', and have created new terms such as 'value co-creation'. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The servitization strategy in healthcare is not a new concept (Yip et al, 2015), and digital servitization has been used as a strategy to enable more fluid and efficient dynamics within the healthcare value chain. In other words, Industry 4.0 opens a new avenue for managing structural capital in healthcare.…”
Section: A Digital Servitization Strategy For Boosting Structural Capitalmentioning
confidence: 99%
“…The servitization strategy in healthcare is not a new concept (Yip et al, 2015), and digital servitization has been used as a strategy to enable more fluid and efficient dynamics within the healthcare value chain. In other words, Industry 4.0 opens a new avenue for managing structural capital in healthcare.…”
Section: A Digital Servitization Strategy For Boosting Structural Capitalmentioning
confidence: 99%
“…This captures a product-service spectrum ranging from customers owning a tangible product with addon services (such as maintenance), through to the sharing and leasing of products, and services that completely replace product ownership (voicemail services). In addition, we introduce two more recent variations from the literature -'Integration-oriented' and 'Service-oriented' (Yip, Phaal, & Probert, 2015).…”
Section: Emerging Product-service Systems In Pharma/healthcarementioning
confidence: 99%
“…Despite the fact that the concept holds great potential to address major challenges within healthcare , PSSs are relatively unexplored in the literature (Mittermeyer, et al, 2011) with limited examples reported (Yip, et al, 2015); (Ryan, et al, 2014); (Velikanov, et al, 2013) (Köbler, et al, 2009) and (Ajai, et al, 2009). In the context of this study Ajai et al, (2009) detail the design of a results-orientated PSS for point-of-care devices, with a case study to collect and transmit health data back to healthcare professionals, enabling the provision of remote services (see Figure 2).…”
Section: Emerging Product-service Systems In Pharma/healthcarementioning
confidence: 99%
“…In order to effectively communicate the information with various stakeholders, to produce insights with respect to the information and to support information-based collaborative work, the information should be well structured and clear, preferably standardized [12][13][14]. An information-driven SA system can be designed as a digital twin of a product-service system and may therefore provide the desired-but challenging to obtain-service context for healthcare product-service system development [15][16][17]. Furthermore, having an SA system which reflects the design of the hospital and its services as well as their up-to-date situation is well aligned with two dominant roles of product-service systems in healthcare: a design tool (e.g., a tool for designing hospital services and business) and a systems thinking decision-support tool [2].…”
Section: Introduction 1operational Motivation and Case Study Backgroundmentioning
confidence: 99%